URANYL SORPTION SPECIES AT LOW COVERAGE ON AL-HYDROXIDE: TRLFS AND XAFS STUDIES - Froideval A.; Del Nero M.; Gaillard C.; Barillon R.; Rossini I.; Hazemann J.L. (My University, 2006)
Detailed understanding of the respective roles of solution and surface parameters on the reactions at uranyl solution/Al-(hydr)oxide interfaces is crucial to model accurately the behaviour of U in nature. We report studies on the effects of the initial aqueous uranyl speciation in moderately acidic solutions, e.g. of mononuclear, polynuclear uranyl species and/or (potential) U(VI) colloids, on the sorption of U by large surface areas of amorphous Al-hydroxide. Investigations by Extended X-ray Absorption Fine Structure (EXAFS) and Time-Resolved Laser-induced Fluorescence Spectroscopy (TRLFS) reveal similar U coordination environments on Al-hydroxide for low to moderate U loadings of sorption samples obtained at pH 4-5, independently of the presence of mononuclear or polynuclear aqueous species, or of the potential instability of initial solutions favoring true U-colloids formation. EXAFS data can be interpreted in terms of a dimeric, bidentate, inner-sphere uranyl surface complex as an average of the U surface structures. TRLFS data, however, provide valuable insights into the complex U surface speciation. They indicate multiple uranyl surface species under moderately acidic conditions, as predominant mononuclear and/or dinuclear, inner-sphere surface complexes and as additional minor species having U atoms in a uranyl (hydr)oxide-like coordination environment. The additional species probably occur as surface polymers and/or as adsorbed true U colloids, depending on the aqueous U concentration level (1-100 ?M). These results are of importance because they suggest that Al-hydroxide surface characteristics strongly control uranyl surface species in moderately acidic systems.
Keywords: COLLOID; FLUORESCENCE SPECTROSCOPY; SORPTION; URANIUM